Essays on sovereign debt crisis - Curado, Thiago Luiz (2019)
This thesis studies novel elements that can affect sovereign debt and default decisions, taking into account the interplays between such factors and indebtedness dynamics. The first chapter studies how a surge in sovereign risk induces trade rearrangements and how this channel affects the economic cost of a debt crisis, shaping sovereign default incentives through the business cycle. The motivation comes from the fact that the European debt crises led to strong response in the exports of the southern European countries; despite the absence of exchange rate devaluations throughout the crisis. To study this issue, I present a general equilibrium model of sovereign default with international trade. The model delivers a structural gravity equation that I use to estimate the trade costs of a debt crisis, validate its key mechanism, and disciplines the calibration of the numerical experiments. Simulation results show that (i) the exports channel is quantitatively relevant, (ii) the final impacts depends on the exports sectoral composition and (iii) beyond the aggregate effects, a debt crisis triggers reallocation both at the industry level and at the firm-level, with non-trivial impacts of the economy’s average productivity. Finally, results suggest that export composition was one of the determinants that contributed to the fact that only Greece ended up defaulting in 2012. The second chapter studies the importance of having flexibility to adjust a broad set of fiscal policy instruments during sovereign debt crises. The motivation comes from the aftermath of Greece’s 2012 sovereign default, when the country had to increase public revenues. Due to a set of exogenous constraints and supranational scrutiny, the adjustment’s burden fell almost exclusively on labor taxes. We build a model of endogenous default with a comprehensive fiscal policy side and with enough structure to allow for heterogeneous impacts of different taxes while keeping computational tractability. The model can replicate the path of the main fiscal variables surrounding the Greek debt restructuring. A key result is that the set of taxes available for policy-making becomes a determinant variable to default decision amid debt crises, even though it plays a minor role during normal times. This contrast reflects the distinct effectiveness of the debt instrument throughout the cycle. Simulations show that this channel is quantitatively relevant for defining default frequencies. Finally, our results suggest an additional channel through which membership in the European Monetary Union may have brought challenges to Greece’s economic recovery following the crisis.